Medical Ceramics from Powders of the System Al2O3–ZrO2–Y2O3 Obtained on an Installation of Nanospray Drying - Lyamina G. V. Galina Vladimirovna; Ilela A. E. Alfa Edison; Dvilis E. S. Edgar Sergeevich; Petyukevich M. S. Mariya Stanislavovna; Tolkachev O. S. Oleg Sergeevich (2018, 2018)
Title screen